Fire Risk Management in Libraries: A Literature Review - Farras Nur Azizah; Katrin Setio Devi (Alexandria: Journal of Library and Information Science, 2024)
The purpose of this research is to describe the actions that can be taken by public libraries to prevent fires, as well as the factors that support and hinder these activities. This is a qualitative study using the literature review method, which involves collecting and analyzing literature as the source of data. A total of 10 articles were analyzed in this research. The fire prevention measures that can be taken by libraries are as follows: (1) regularly inspecting the building's condition, electrical systems, emergency exits, and the availability of fire extinguishing equipment; (2) storing flammable materials outside the main building; (3) implementing a no-smoking policy within the library premises; (4) turning off unnecessary electronic devices after closing hours; (5) establishing a fire disaster management committee; (6) creating a communication network and a list of contacts for fire disaster response services; (7) distributing firefighting equipment; (8) conducting training on fire disaster response procedures for all library staff. Factors that can support the preparedness of public libraries in dealing with fires are (1) an adequate number of fire-fighting equipment that is regularly inspected; (2) conducting training for staff on fire disaster response procedures by the local fire department; (3) the existence of fire response Standard Operating Procedures (SOP) that comply with safety standards and building conditions. On the other hand, factors hindering fire preparedness efforts in public libraries are (1) lack of knowledge about fires; (2) insufficient training to deal with fires; (3) staff indifference in taking preventive measures and preparations for fire disasters.